2004
DOI: 10.1021/jf0490551
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Pu-erh Tea on Oxidative Damage and Nitric Oxide Scavenging

Abstract: The effects of pu-erh tea, which is prepared by fermentation of tea, on oxidative damage and nitric oxide scavenging, compared with various other brands of tea were investigated. The total antioxidant activity was determined using the Trolox equivalent antioxidant capacity (TEAC) assay. The results showed that TEAC values of the 200 microg/mL water extracts of pu-erh tea (WEPT), green tea, oolong tea, and black tea were 86.3, 85.3, 87.4, and 80.3 (microg/mL), respectively, indicating that WEPT showed a signifi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
112
3
3

Year Published

2009
2009
2019
2019

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 121 publications
(123 citation statements)
references
References 44 publications
5
112
3
3
Order By: Relevance
“…given diet including some common fruits, vegetables and beverages [12]. The presented herb teas have various effects [13][14][15][16][17][18][19][20][21][22]. Tables 1 and 2 show that some of them, Arabian jasmine, Guava, Hardy rubber tree, Japanese persimmon, Oolong tea and Puerh tea, have high total polyphenol content and antioxidant activities.…”
Section: Discussionmentioning
confidence: 99%
“…given diet including some common fruits, vegetables and beverages [12]. The presented herb teas have various effects [13][14][15][16][17][18][19][20][21][22]. Tables 1 and 2 show that some of them, Arabian jasmine, Guava, Hardy rubber tree, Japanese persimmon, Oolong tea and Puerh tea, have high total polyphenol content and antioxidant activities.…”
Section: Discussionmentioning
confidence: 99%
“…Pu-erh tea is a Chinese tea made from green tea leaves that have been oxidized and fermented using micro-organisms such as Aspergillus species. Several studies have reported that Pu-erh tea has the ability to reduce body weight, fatty acid synthesis, hyperlipidaemia, NAFLD and oxidative stress [6][7][8][9][10][11][12][13]. However, the mechanisms underlying Pu-erh tea's alleviation of these metabolic processes and symptoms are not clear.…”
Section: Introductionmentioning
confidence: 99%
“…Owing to the much lower consumption of post-fermented tea, the chemical composition of this tea has not been characterized in detail. However, recent studies suggest some beneficial effects of post-fermented tea (Chiang, Weng, Lin-Shiau, Kuo, Tsai, & Lin, 2006;Duh, Yen, Yen, Wang, & Chang, 2004;Kuo, Weng, Chang, Tsai, Lin-Shiau, & Lin, 2005;Noguchi, Hamauzu, & Yasui, 2008;Oyaizu, Hotsumi, Takagi, Matsumoto, Fujita, Matsuzaki, & Yamashita, 2005;Oyaizu, Hotsumi, Takagi, Matsuzaki, Yamashita, Takenaga, & Itho, 2006). Black and oolong tea production includes a process called "tea fermentation", in which constituents of fresh tea leaves are chemically altered by enzymes originally contained in the leaves (Roberts, 1962;Tanaka, Matsuo, & Kouno, 2010).…”
Section: Introductionmentioning
confidence: 99%